An Impact of Cobalt on Freshwater Phytoplankton in Warming Polar Regions? - Kechen Zhu; Jana Krause; Camila Marín‐Arias; Mireia Mestre; Juan Höfer; Thomas J. Browning; Eric P. Achterberg; Mark J. Hopwood (Geophysical Research Letters)
Abstract Polar freshwater ecosystems are sensitive to climate change, facing increasing temperatures and its consequences such as glacier retreat. Phosphorus and/or fixed nitrogen are widely expected to limit primary production in most freshwater environments, however the role of micronutrients is largely un‐characterized. We measured dissolved nitrate and nitrite, phosphate, cobalt, iron, manganese and zinc in a selection of Greenland and Antarctic lakes, and report the first evaluation of cobalt regulating phytoplankton growth in these systems using bioassay incubations. Results showed cobalt potentially co‐limited phytoplankton in three of the eight sites tested. A time‐series of dissolved cobalt measured in Kobbefjord (southwest Greenland) runoff corroborated low cobalt availability during summer. This was in contrast to manganese and iron which remained at high concentrations throughout summer. We hypothesize that high manganese:cobalt and/or zinc:cobalt ratios in runoff, may impede cellular cobalt acquisition, meaning cobalt co‐limitation of primary production is plausible in many polar freshwater environments.